A New Engineering Model of Lightning M Component That Reproduces Its Electric Field Waveforms at Both Close and Far Distances. Issue 24 (16th December 2019) - Azadifar, Mohammad; Rubinstein, Marcos; Li, Quanxin; Rachidi, Farhad; Rakov, Vladimir
Abstract: We present a new engineering model for the M component mode of charge transfer to ground that can predict the observed electric field signatures associated with this process at various distances, including (a) the microsecond‐scale pulse thought to be due to the junction of in‐cloud leaders and the grounded, current‐carrying channel and (b) the ensuing slow, millisecond‐scale pulse due to the M component proper occurring below the junction point. We examine the features of 13 microsecond‐scale, fast electric field pulses associated with M component processes in upward negative lightning initiated from the Säntis Tower and recorded 14.7 km from it. Eleven out of the 13 pulses were found to be unipolar with pulse widths in the range of 9.8 to 35 μs, and the other two were bipolar. To model the process that gives rise to microsecond‐scale pulses, we hypothesize that the current pulses propagating away from the junction point along the main lightning channel (below the junction point) and along the feeding in‐cloud leader channel (branch) carry the same amount of charge. We further assume that the pulse traversing the branch is similar to a subsequent return‐stroke (RS) pulse. In the model, the RS‐like process is represented by the MTLE model. The millisecond‐scale field signature that follows the initial fast pulse in M components at close distances is simulated in our model using the guided‐wave M component model. The proposed model successfully reproduces the vertical electric field waveforms associated with M‐component processes in upward lightning flashes initiated from the Säntis Tower at 14.7‐km distance from the lightning channel, in which both the fast, microsecond‐scale and the following slower, millisecond‐scale pulses were observed. The model also reasonably reproduces the known features of electric field signatures at close distances (up to 5 km), where the amplitude of the millisecond‐scale hook‐like pulse is much larger than that of the microsecond‐scale pulse, and at far distances (of the order of 100 km), where the microsecond‐scale pulses are dominant. Key Points: The new engineering M component model can reproduce the microsecond‐scale electric field pulses thought to be due to the junction process The proposed model can be used to simulate both the microsecond‐ and millisecond‐scale features of M component field signatures at close and far ranges The geometry of the in‐cloud leader channel and the junction point height largely determine the presence of the microsecond‐scale electric field pulses